2009
DOI: 10.1186/1750-4732-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Muscle functional magnetic resonance imaging and acute low back pain: a pilot study to characterize lumbar muscle activity asymmetries and examine the effects of osteopathic manipulative treatment

Abstract: Background: Muscle functional magnetic resonance imaging (mfMRI) measures transverse relaxation time (T2), and allows for determination of the spatial pattern of muscle activation. The purposes of this pilot study were to examine whether MRI-derived T2 or side-to-side differences in T2 (asymmetries) differ in low back muscles between subjects with acute low back pain (LBP) compared to asymptomatic controls, and to determine if a single osteopathic manipulative treatment (OMT) session alters these T2 properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Several studies have noted reduced paraspinal muscle activity following thrust based MT (i.e., HVLA spinal manipulation) of individuals with LBP (DeVocht et al, 2005;Ellestad et al, 1988;Krekoukias et al, 2009;Lehman et al, 2001), and we recently reported that a combination of MT's (incorporating both thrust and non-thrust MT) normalizes side-to-side differences in the muscle activation patterns of trunk muscles of individuals with sub-acute LBP (Clark et al, 2009). Additionally, we also recently reported that thrust based MT did not systematically alter the erector spinae stretch reflex amplitude in patients with chronic LBP or asymptomatic controls, but that in study participants exhibiting an audible response to manipulation the stretch reflex was reduced $20% .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have noted reduced paraspinal muscle activity following thrust based MT (i.e., HVLA spinal manipulation) of individuals with LBP (DeVocht et al, 2005;Ellestad et al, 1988;Krekoukias et al, 2009;Lehman et al, 2001), and we recently reported that a combination of MT's (incorporating both thrust and non-thrust MT) normalizes side-to-side differences in the muscle activation patterns of trunk muscles of individuals with sub-acute LBP (Clark et al, 2009). Additionally, we also recently reported that thrust based MT did not systematically alter the erector spinae stretch reflex amplitude in patients with chronic LBP or asymptomatic controls, but that in study participants exhibiting an audible response to manipulation the stretch reflex was reduced $20% .…”
Section: Discussionmentioning
confidence: 92%
“…We further hypothesized that this observation was mechanistically driven by the MT's acting to attenuate the gain of the muscle spindle afferents and reduce reflexive contractile activity. Indeed, many scientists and clinicians have long-postulated that MT's exert their biologic effects on the nervous system (Clark et al, 2009;Cote et al, 1994;Dishman et al, 2008;Johansson and Sojka, 1991;Knutson, 2000;Korr, 1975;Pickar, 2002;Sung et al, 2005;Terrett and Vernon, 1984;Vernon et al, 1990). For example, more than three decades ago it was hypothesized that MT's mechanistically act by reducing the gain, or sensitivity, of the monosynaptic stretch reflex (a.k.a., myotatic reflex, deep tendon reflex) (Korr, 1975).…”
Section: Introductionmentioning
confidence: 96%
“…The muscles of the lateral abdominal wall (OT: external oblique, internal oblique, and transversus abdominis) and quadratus lumborum (QL) play an important role during kicking and tennis strokes (Raty et al, 1999;Chow et al, 2009). The asymmetric hypertrophy of these muscles may increase the risk of low back pain (Hides et al, 2008;Clark et al, 2009). It remains to be determined whether tennis and soccer practice elicits the hypertrophy of QL and the muscles of the lateral abdominal wall.…”
Section: Introductionmentioning
confidence: 98%
“…Given this link, it is unsurprising that multifidus alterations can be predictive of different spinal injuries [9]. Habitual techniques used to measure multifidus activation [16][17][18][19] are electromyography, ultrasound, MRI, manual techniques. Among the latter, we have identified the technique that will form the focus of the current study, namely that of muscular activation (MAT ® …”
Section: Introductionmentioning
confidence: 99%